BUSINESS REVERSE LOGISTICS MANAGEMENT AND STRATEGIES: SUSTAINABILITY AND OPERATIONAL EFFICIENCY - Ferreira de Oliveira, Lincoln (Revista Gênero e Interdisciplinaridade, 2024)
In the production market, sustainability has been put on the agenda, given the high consumption demand, which creates harmful risks for the environment, many of which are caused by the irregular disposal of final raw materials, especially those that are difficult to decompose. This scenario reflects on production engineering requiring new sustainable redirection, which has been mediated by the practice of reverse logistics, already adopted by large companies in the production sector. Reverse logistics strategies can not only bring sustainable benefits, but also increase a company’s operational efficiency. The general objective of this research was to analyze the contributions of reverse logistics to business management with an emphasis on sustainability and productive efficiency. The literature review methodology was used to support the research with results extracted from 15 other scientific studies, searched in the Google Scholar and SciELO databases, published between the years 2019 and 2024 – with some exceptions –, in the language Portuguese. This was a qualitative research study, of a basic nature, with descriptive objectives and a literature review procedure. The results found demonstrated that some reverse logistics strategies, such as collection and recycling programs, reconditioning and reuse, waste management and others, increase operational efficiency, reducing costs and, in addition, produce environmental responsibility for the image of companies. productive organizations. The research was concluded on the importance of implementing and managing reverse logistics within production engineering, thus meeting the innovations of market demands.